Pembuatan Media Pembelajaran Flashcard Hijaiyah Dalam Pemberian Materi Pengajaran Al-Qur’an Untuk Meningkatkan Nilai Agama dan Moral Anak Di PAUD Al-Ghofari - Pelawi, Siti Alawiah Biastri; Rosmidar, Rosmidar; Siregar, Anggita Pratiwi; Harahap, Nurhamdah (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2025)
This community service report presents a comprehensive analysis of the effectiveness of Hijaiyah flashcards in teaching the Quran to early childhood, with a focus on enhancing religious and moral values. Reviewed research consistently shows that the use of flashcards significantly improves recognition of the Hijaiyah letters and the ability to read the Quran, transforming previously monotonous learning into more engaging and enjoyable learning. Furthermore, this medium has proven effective in instilling an understanding of religious concepts and abstract moral values ​​such as honesty, discipline, and compassion, by harnessing the power of visual stimulation and active interaction. However, successful implementation depends heavily on the capacity and readiness of teachers, the learning environment, and the ability to accommodate individual differences. This report recommends a holistic approach that includes teacher professional development, strategic classroom management, and adequate resource allocation to maximize the potential of flashcards in supporting the holistic development of early childhood.